(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
Based on ergonomics, this paper analyzes the foot structure, physiological and psychological needs of people with lower limb disability, and applies the concept of ergonomics to design, so as to optimize the functionality of shoes in terms of easy wear (putting clothes on and off), comfort, stability and protection. The ergonomic design scheme presented in this paper could provide shoes for them that conform to their foot structure and behavior characteristics, which are really comfortable and healthy. At the same time, it can also provide a more e±cient and feasible design direction for the market, which has certain value for the further in-depth development and application.